Magnetic Damping For Maglev - S. Zhu; Y. Cai; D.M. Rote; S.S. Chen (Shock and Vibration)
Magnetic damping is one of the important parameters that control the response and stability of maglev systems. An experimental study to measure magnetic damping directly is presented. A plate attached to a permanent magnet levitated on a rotating drum was tested to investigate the effect of various parameters, such as conductivity, gap, excitation frequency, and oscillation amplitude, on magnetic damping. The experimental technique is capable of measuring all of the magnetic damping coefficients, some of which cannot be measured indirectly.